Saúde do trabalhador e economia solidária: aproximações no projeto Esperança/Cooesperança - Zeni, Mônica Rosa (2010)
Solidarity economy is a form of social organization based on collaborative work and networking, it s an alternative economy that became a reality amid the current capitalist logic. It s a proposal that provides a new orientation of life space and social interactions, from a perspective of sustainable development, solidarity and quality of life. Considering that the social and economic organization allows different work processes and standards of living, this study sought to relate workers health conditions to their participation into a solidarity initiative. Considering the discursive approach through Brazilian public policies of solidarity and health, the present research aimed to investigate its relationships and possibly effectiveness by making interviews and analysing testimonials from people involved in a solidarity project called Feirão Colonial Projeto Esperança/Cooesperança, created in Santa Maria, Brazil. In order to reach this goal, a health/ecosystem approach were used to guide and analyze the content of the interviews which were carried out with leaders, farmers and consumers. The results showed that there is a close relation between health and work, and how important it is to have a well organised productive chain followed by a logic based on solidarity economy. In addition to this perspective this assignment could show how important and influential is this new social organization in providing improvements in workers health conditions.